S. Müth, P. I. Schneider, M. Schnelle, P. D. DeStaebler (eds) Ancient Fortifications. A Compendium of Theory and Practice. - Lohmann, Hans (Journal of Greek Archaeology, 2017)
Fortifications of different kinds and various ages are handed down to us all over the world in great numbers, frequently in excellent state of preservation and sometimes also of remarkable aesthetic qualities. Since prehistoric times they did not only determine the appearance of settlements, towns, and landscapes, but also the life of the inhabitants – economically, politically, and socially. Nonetheless, for any number of reasons, mostly founded in the history of the different archaeological disciplines, the systematic study of ancient fortifications did not keep up with the scientific research on ancient settlements or works of art.